Technology Integration in Tourism Management: Enhancing the Visitor Experience - Berlin Any; Sweety Four; Chloe Tariazela (Startupreneur Business Digital (SABDA Journal), 2024)
This research aims to investigate the integration of technology in tourism management with a focus on improving the visitor experience. The background is related to the rapid development of technology and its impact on the tourism industry, where the use of technology can influence the way tourism destinations are promoted, managed, and enjoyed by visitors. The aim of this research is to identify gaps in knowledge related to the implementation of technology in tourism management and to evaluate the effectiveness of various technological methods in improving the visitor experience. This research method includes literature analysis, case studies, and surveys to collect data on the use of technology in tourism management. It is hoped that the results of this research will provide new insights into the potential of technology to improve visitor experiences in tourism destinations, as well as its practical implications for the tourism industry. The implication of this research is to provide guidance for tourism practitioners in designing more effective strategies for integrating technology in destination management, which in turn can increase the competitiveness and sustainability of tourism destinations. The uniqueness of this research lies in its interdisciplinary approach that combines the fields of technology and tourism management, as well as its focus on visitor experience as a key aspect in the success of modern tourism destinations.